An Application of Image Processing for Conservation of Natural Life - İsmail SARİTAS; İlker Ali OZKAN; Tahir SAG (International Journal of Applied Methods in Electronics and Computers, 2015)
In this study; a station has been set up containing three cameras, a wifi antenna, a solar power panel and a wind tribune in the wild sheep natural preservation area. To store and process the data collected by the system a unit consisting of a wifi receiver and computer are established in Technology Faculty of Selcuk University. The study are performed on the transferred images in the central unit by using image processing techniques of MATLAB software. In this study, image enhancement process are performed and the best images focused on Anatolian wild sheep are acquired. Improved static images are used for the determination of where the Anatolian wild sheep on the picture, area occupied by the sheep in pixels and number of the sheep by using the techniques of picture partitions.